Skeletal Expansion with GSR Expander (Orthodontic Journal of Nepal, 2021)
This article reports two cases treated with a modified Miniscrew Assisted Rapid Palatal Expander (MARPE) that was fabricated in-office. Two female patients aged 15 years and 18 years were treated for maxillary expansion. An in-office modified GSR Expander was used. The appliance was secured in the patient’s maxillary arch using four miniscrews. Expansion was carried out for 4 weeks and 2 weeks respectively. Considerable opening of mid palatal suture with skeletal expansion was observed. An economical and effective alternative to stock made MARPE with better adaptability and clinical modifiability.